2021
DOI: 10.1002/cam4.4433
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive treatment experience of anal squamous cell carcinoma from a tertiary cancer center in South China

Abstract: Background Anal squamous cell carcinoma (ASCC) is a rare malignant tumor with increasing incidence. The goal of our study was to analyze the treatment outcome and prognostic factors of ASCC in South China in the past half‐century. Methods This study retrospectively included 59 patients with ASCC admitted from 1975 to 2018 in Sun Yat‐sen University cancer center. The clinical records and follow‐up information of all patients were collected. Survival analysis and univariate and multivariate regression analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The prognosis of ASCC is largely influenced by multiple factors including nodal involvement, tumour size, skin ulceration, gender and HPV. Yuan et al [ 13 ] reported the differences in 5-year survival rates between node-negative and node-positive disease (76.7% versus 70.3%), and between stages I–II and stages III–IV (83.6% versus 71.2%), respectively. Esin et al [ 14 ] also reported an improvement in progression-free survival (PFS) with a lower T stage [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of ASCC is largely influenced by multiple factors including nodal involvement, tumour size, skin ulceration, gender and HPV. Yuan et al [ 13 ] reported the differences in 5-year survival rates between node-negative and node-positive disease (76.7% versus 70.3%), and between stages I–II and stages III–IV (83.6% versus 71.2%), respectively. Esin et al [ 14 ] also reported an improvement in progression-free survival (PFS) with a lower T stage [ 14 ].…”
Section: Discussionmentioning
confidence: 99%